2015
DOI: 10.1002/alr.21537
|View full text |Cite
|
Sign up to set email alerts
|

Purely endoscopic endonasal surgery of the craniovertebral junction: A systematic review

Abstract: Our analysis found that EES of the CVJ results in a high rate of neurologic improvement with acceptable complication rates. Given its minimally invasive nature and high success rate, this approach appears to be a reasonable alternative to the traditional transoral approach in select cases. This study represents the largest pooled sample size of EES of the CVJ to date. Increasing use of the endoscopic endonasal approach will allow for further studies with greater statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
(66 reference statements)
0
18
0
1
Order By: Relevance
“…A welldocumented complication of the transnasal approach is cerebrospinal fluid (CSF) leak, so although they are notoriously difficult to repair, the use of autologous fat grafts and fibrin glue has been used with some success. [2,3,6,9,40] As with any new technique, there is a learning curve associated with adoption of ETO [18]. The average surgical time of ETO was 356.4 min in one study, whereas the average time with the transoral approach was only 141 minutes in another [18,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A welldocumented complication of the transnasal approach is cerebrospinal fluid (CSF) leak, so although they are notoriously difficult to repair, the use of autologous fat grafts and fibrin glue has been used with some success. [2,3,6,9,40] As with any new technique, there is a learning curve associated with adoption of ETO [18]. The average surgical time of ETO was 356.4 min in one study, whereas the average time with the transoral approach was only 141 minutes in another [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,6,9,40] As with any new technique, there is a learning curve associated with adoption of ETO [18]. The average surgical time of ETO was 356.4 min in one study, whereas the average time with the transoral approach was only 141 minutes in another [18,37]. Though surgical length will vary among practitioners, with experience and further refinements to instrumentation and navigation, operative times will likely decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karligkiotis et al 14 report on their experience utilizing a pedicled nasoseptal flap to maintain patency of the endoscopically-created opening, and demonstrate significant success. Fang et al 15 review the literature regarding endoscopic endonasal surgery of the craniovertebral junction and confirm the efficacy of the approach and a relatively low complication rate. The most common postoperative complication was respiratory obstruction, and there was a 7% incidence of postoperative tracheotomy.…”
mentioning
confidence: 87%
“…Endoscopic endonasal transclival and transodontoid approaches are now routinely performed in leading skull base centers and have become an alternative to the transoral approach that historically has been the gold standard. Hence, in a recent systematic review evaluating purely endoscopic endonasal surgery of the CCJ, Fang et al noted that these approaches resulted in a high rate of neurologic improvement and acceptable complications rate, and concluded that endoscopic endonasal approaches to the CCJ appeared to be a reasonable alternative to the traditional transoral approach in certain cases . These approaches usually involve a posterior bony and mucosal septectomy, which may compromise the integrity of the posterior nasal septum and damage the vascularized pedicled nasoseptal flap (PNSF), a robust reconstructive option that has become the workhorse for repair of large skull base defects over the last 10 years .…”
Section: Introductionmentioning
confidence: 99%